Asylum seekers in the global context of xenophobia: Introduction to the special issue. (March 2020) - Poynting, Scott; Briskman, Linda
In 2015 the global media fixated on the 'Syrian crisis' that became the 'refugee crisis' for Europe. This construction of crisis was Eurocentric, temporally narrow and presented as problem for European nation states. We view the 'problem' rather as the nationalism and racism of receiving countries with a resurgence of a discourse of ethno-nationalist European identity sharpened by the global financial crisis and neoliberal austerity. Despite disparate national histories, we discern: a 'blame-the-victim' tendency to view those most harmed by the 'refugee crisis' as the 'problems' that constitute it; a state-centred perspective that requires the 'problem' to be addressed by nation states; a 'charity starts at home' ideology, usually from those sectors of society that are least willing to extend compassion 'at home'; a systemically cruel state disposition towards asylum seekers as part of a regime of deterrence from seeking asylum in that state; a racialised and gender-blinkered regime of determination of refugee status; a politically opportunist populism that deploys ethno-nationalist 'othering' or scapegoating in times of economic distress and political instability; a wilful and convenient blindness to the histories of the contemporary conflicts as the legacies of colonialism; a globalised Islamophobia, casting Muslim asylum seekers as a potential security threat and undermining of national (or 'western', or civilisational) values; a gender-inflected racialisation that demonises the asylum-seeking other as hyper-patriarchal and occludes or minimises the patriarchy of the 'civilised' west. *repeats six paras on*